"We Likkle, but We Tallawah": Maintaining Competitive Advantage in the Crowded Specialty Coffee Market. Issue 1 (2nd January 2017) - Mighty, Mario A.
ABSTRACT: The Jamaican coffee industry (JCI) has exhibited key characteristics of what it means to have a competitive advantage (CA) for a number of decades. However, the last 5–10 years have seen strong challenges to this CA. The author explores the deeper dynamics of these challenges using a five forces analysis as developed by Michael Porter in addition to a thematic analysis of semistructured interviews and data from various local and international coffee organizations to assess the various forces of the model. It was revealed that the unique nature of the JCI's product led to moderate bargaining power as a supplier, which acted as an effective buffer to the high bargaining power of global coffee buyers. These findings highlighted the importance of seeking new markets and embedding symbolic attributes as part of the overarching drive to maintain viability within specialty product markets.